Comprehensive analysis of endoplasmic reticulum-related and secretome gene expression profiles in the progression of non-alcoholic fatty liver disease - Gao, Rong; Wang, Jin; He, Xuemin; Wang, Tongtong; Zhou, Li; Ren, Zhitao; Yang, Jifeng; Xiang, Xiaoxin; Wen, Shiyi; Yu, Zhuojun; Ai, Heying; Wang, Yuchan; et al. (Frontiers in Endocrinology, 2022)
Endoplasmic reticulum (ER) is the principal organelle for protein synthesis, such as hepatokines and transmembrane proteins, and is critical for maintaining physiological function. Dysfunction of ER is associated with metabolic disorders. However, the role of ER homeostasis as well as hepatokines in the progression of non-alcoholic fatty liver disease (NAFLD) remains to be elucidated. Here we comprehensively analyzed the RNA-seq profiles of liver biopsies from 206 NAFLD patients and 10 controls from dataset GSE135251. The co-expression modules were constructed based on weighted gene co-expression network analysis and six co-expression modules were identified, of which brown module stood out to be significantly associated with fibrosis stage and NAFLD activity score (NAS). Subsequently, cytoscape with cytoHubba plugin was applied to identify hub genes in the brown module. GO and KEGG enrichment analysis of the top 20 hub genes were performed and showed the involvement in the process of extracellular matrix formation, collagen synthesis and decomposition, etc. Further, the expression of the top 20 hub genes were found to be a consistent increasing trend as the fibrosis stages and NAS increased, which have been validated both in HFD fed and HFHC fed mice. Among these genes, THY1, PTGDS, TMPRSS3, SPON1, COL1A2, RHBDF1, COL3A1, COL5A1, COL1A1 and IGFBP7 performed well in distinguishing fibrosis stage, while COL1A2, COL3A1, THY1, RHBDF1 and COL1A2 exhibited good capacity to discriminate NAS. Besides, RHBDF1, COL3A1, QSOX1, STING1, COL5A1, IGFBP7, COL4A2, COL1A1, FKBP10 and COL1A2 also showed a strong power in the diagnosis of NAFLD. In addition, COL1A1, COL1A2, COL3A1, COL8A2, IGFBP7, PGF, PTGDS, SPON1, THY1 and TIMP1were identified as secretome genes from the top 20 hub genes. Of them, circulated Thy1 and collagen III level were validated to be significantly elevated in the MCD diet induced mice. Thus, we provided a systemic view on understanding the pathological roles and mechanisms of ER as well as secretome in NAFLD progression. THY1, COL1A1, COL1A2, COL3A1 and RHBDF1 could be served as candidate biomarkers to evaluate the progression of NAFLD.